A multi-objective optimization design of industrial robot arms - Kouritem, Sallam A.; Abouheaf, Mohammed I.; Nahas, Nabil; Hassan, Mohamed (Alexandria engineering journal, 2022)
This paper introduces a multi-objective design mechanism to minimize both the initial and running costs of industrial robot arms. The goal of the design problem is to decide the type of material and physical dimensions of the robot arm to withstand high loads at vulnerable locations using stress analysis. Additionally, it selects the material architecture for the robot links based on a vibration analysis to avoid robot failure at or close to the resonance frequency. Hence, a set of design equations based on stress analysis are developed using analytical approaches while the findings are supported by finite element simulations in ANSYS. These decide the type of material, cross-section area, factor of safety (FoS), and maximum deflection of the robot links in terms of the mass-loads. Moreover, the vibration analysis is conducted to enhance the dynamic characteristics of the robot arm. Therefore, the excitation frequency is modified by changing the mass and the robot segment-material to evade working at the natural frequency. Modal analysis is conducted using ANSYS to identify the fundamental frequencies and their modal shapes. Then, a material selection mechanism based on finite element analysis is considered to allow a safe frequency operation range for the robot arm. A customized robot arm structure that combines Magnesium and Aluminum alloy with highly improved FoS and minimizes the initial and operating costs is proposed. In addition to the body structure of the robot arm, the influence of the reducers and motors on the stiffness and vibration of the robot arm is presented. Finally, the motion of the robot arm is optimized using a Genetic Algorithm subject to a set of boundary conditions imposed by the desired mission. The effect of rotation angle value in the power consumption is presented. The coefficients of a developed angular displacement function are optimized to ensure minimum power consumption during the robot missions.